2017
DOI: 10.1186/s12882-017-0636-0
|View full text |Cite
|
Sign up to set email alerts
|

Response to immunosuppressive therapy in PLA2R- associated and non-PLA2R- associated idiopathic membranous nephropathy: a retrospective, multicenter cohort study

Abstract: BackgroundAccording to renal M type phospholipase A2 receptor (PLA2R) immunohistochemistry, idiopathic membranous nephropathy (IMN) could be categorized into PLA2R-associated and non-PLA2R-associated IMN. We conducted a retrospective, multicenter cohort study with 91 patients to compare the effect of immunosuppressive therapy between PLA2R-associated and non-PLA2R-associated IMN patients.MethodsA total of 91 biopsy-proven IMN patients from Huashan hospital and People’s Hospital of Wuxi in past 5 years were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…The relevant antibodies can be detected in the circulation of patients with iMN, and they form in situ immune complexes in the glomerular subepithelium, damaging podocytes via membrane attack complexes to induce proteinuria [12]. Given its high sensitivity and specificity, the presence of PLA2R in the glomerulus has guiding significance in the diagnosis and evaluation of iMN [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The relevant antibodies can be detected in the circulation of patients with iMN, and they form in situ immune complexes in the glomerular subepithelium, damaging podocytes via membrane attack complexes to induce proteinuria [12]. Given its high sensitivity and specificity, the presence of PLA2R in the glomerulus has guiding significance in the diagnosis and evaluation of iMN [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study included 572 IMN patients had found that patients who did not achieve remission had a higher positive rate of renal PLA2R antigen than those achieved remission . Another retrospective cohort study had also identified a higher remission rate in non‐PLA2R‐associated IMN . The reason for lower probability to achieve remission in PLA2R‐associated IMN patients still remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…25 Another retrospective cohort study had also identified a higher remission rate in non-PLA2R-associated IMN. 26 The reason for lower probability to achieve remission in PLA2R-associated IMN patients still remained unclear. Autoantibody may target a specific conformational region of PLA2R protein on the podocyte surface and trigger the formation of immune complexes, which may lead to the activation of complement pathway and the enhancement of glomerular permeability to plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…As compared to patients with non-PLA2R1 related MN, those with PLA2R1 related MN responded slower to immunosuppressive therapy [ 135 , 136 ]. Moreover, patients presenting high titer of autoantibodies have more severe disease and a longer time to disease remission [ 137 ].…”
Section: Anti-pla2r1 and Anti-thsd7a Antibodies And Primary Mnmentioning
confidence: 99%